Cylinder-wall interference effects on finite-length wavy cylinders at subcritical Reynolds number flows - New, T. H. (2013)
An experimental study was conducted on aspect-ratio of six finite-length wavy cylinders immersed within a Re D = 2,700 free-stream. Wavelengths of 2 and 4 diameters, as well as wave amplitude of 0.1, 0.2 and 0.3 diameters were used for a comprehensive investigation. Time-resolved particle-image velocimetry measurements and proper orthogonal decomposition analyses show that for the present large wavelength wavy cylinders, vortex-shedding behaviour of high aspect-ratio wavy cylinders observed in past studies can be altered through variations in the aspect-ratio, exact geometric node and saddle locations, as well as the presence of end-walls. This is due to the persistent formation of recirculating regions close to the end-walls under certain wavy cylinder configurations, which affect the distributions of spanwise flows and vortex formation lengths. Vortex-shedding behaviour of smaller-wavelength wavy cylinders has also been observed to be considerably less sensitive to variations in the physical configurations, due to the formation of multiple streamwise vortices at the saddles. The presence of these coherent streamwise vortices is postulated to play a key role in significantly reducing flow-altering effects associated with the end-walls.